Surgical intervention for traumatic facial paralysis: an analysis of 15 patients - Baysal, Elif; Gülşen, Secaattin; Aytaç, İsmail; Çıkrıkçı, Sercan; Gönüldaş, Burhanettin; Durucu, Cengiz; Mumbuç, Semih; Kanlıkama, Muzaffer (ENT Updates, 2016)
Objective: The aim of the present study was to analyze patients who underwent facial nerve decompression. Methods: A retrospective data analysis was performed on 15 patients operated between January 2005 and January 2015. All patients were evaluated with high-resolution temporal computed tomography, House-Brackmann grading system, and electrodiagnostic tools (electromyography or electroneurography). Results: There were 8 female and 7 male patients with a mean age of 20.56 (range: 2 to 59) years. All of the patients underwent facial decompression surgery via a transmastoid approach. Conclusion: Transmastoid approach in patients with facial nerve injuries within the first genu and the digastric ridge is appropriate, and the increase in the amplitude observed in the postoperative EMG records obtained from musculus orbicularis oculi may be considered as significant indicator of nerve recovery that occurs before clinical improvement.